VOLCANIC – SEDIMENTARY METAL DEPOSITION IN PALEOMARGIN ENVIRONMENT: A “ PROTORE ” OCCURRENCE IN CENTRAL SARDINIA (ITALY) - Fadda, S.; Fiori, M.; Pretti, S.; Valera, P. (Bulletin of the Geological Society of Greece, 2010)
Several metallogenic periods took place at different moments of the geological evolution of Sardinia, but at places they interacted: the close correlation between the metal parageneses in the Ordovician – Silurian sequences, outcropping in the central part of the island, and the veins and masses associated with the Hercynian magmatism is depicted. The volcanic-sedimentary mixed-sulphide lenses contained in Silurian occurrences show clear sedimentary structures, and the connection with coeval volcanics seems evident. These mineralizations are thought to be the protores for the subsequent metallogenic cycle related with the Hercynian orogenesis which had a strong effect as a promoter of the remoulding of preexisting mineral concentrations to give new ore- and industrial minerals deposits. Several geochemical campaigns have covered the entire island, and wide areas of the Paleozoic basement, mostly localised in the internal zones, showed high base- and heavymetals contents. A new prospecting programme has been started in Central Sardinia; it follows the ore-bearing horizon along the Ordovician-Silurian boundary with the purpose to better understand these primary metal depositions, their relationships with geodynamic structures, and ore mobilisation caused by the Hercynian granites. The geochemical anomalies along this horizon detected in the area of “Castello Medusa” support detailed prospecting works.